Mother's self efficacy and perceived barriers in maintaining dental health of pre-school children - Chairunisa, Fania (BKM Public Health and Community Medicine, 2021)
Purpose: The purpose of this study was to analyze the relationship between mothers’ self-efficacy and perceived barriers to mothers in maintaining the dental health of children with caries status in pre-school children. Method: This study is an observational study with a cross-sectional research design, conducted in the city of Yogyakarta from May to June 2021. The sample in this study amounted to 119 pairs of mothers and children aged 2-6 years. The sampling technique used was multistage cluster random sampling by randomizing the districts and early childhood education organizations (PAUD). Because it is still during the Covid-19 pandemic, data collection is carried out remotely using online questionnaires and the teledentistry method. Data analysis used the Spearman correlation test to determine the relationship between self-efficacy also perceived barriers to dental caries status. Multivariate analysis using multiple linear regression was carried out to analyze the influence of self-efficacy and perceived barriers with caries status in pre-school children. Results: Self efficacy has no effect on dental caries status (r = - 0.107; p = 0.248), as well as perceived barriers (r = 0.108; p = 0.240). Mother's self efficacy and perceived barriers simultaneously did not affect the child's dental caries status (R square = 0.021; p = 0.284). Conclusion: The results showed that there was no significant relationship and influence between self-efficacy and perceived barriers with dental caries status separately or simultaneously. Further research is needed using larger sample size and more variables to obtain comprehensive results.